Directed CH Alkenylation of Quinoline N‐Oxides at the C‐8 Position Using a Cationic Rhodium(I) Catalyst. Issue 7 (30th April 2014) - Shibata, Takanori; Matsuo, Yusuke
Abstract: The cationic rhodium‐catalyzed alkenylation proceeds at the C‐8 position of quinoline N ‐oxides. Regioselective CH bond activation was achieved by the directing effect of the anionic oxygen of an N ‐oxide moiety, which can be readily removed by reductive treatment. A variety of 8‐alkenylated quinoline N ‐oxides was obtained in moderate to high yields. Abstract :